2018
DOI: 10.1371/journal.pone.0193958
|View full text |Cite
|
Sign up to set email alerts
|

Grass pollen production and group V allergen content of agriculturally relevant species and cultivars

Abstract: Grass pollen is the main cause of hay fever and allergic asthma in warm temperate climates during summer. The aim of this study was to determine the content of group 5 major allergens in pollen grains of agriculturally important grass species/cultivars. For each cultivar flowering dates and pollen production of cut anthers were observed in the field and in a climate chamber, respectively. An ELISA was used to quantify the group 5 allergens (Phl p5) in pollen extracts which were gained from the grass species Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…In-situ pollen collections are very likely to be influenced by humidity (e.g. caused by rain events), mildew and insects after plants have been covered with collective containers [ 38 ]. To overcome these issues, grasses were kept in climate chambers during the actual pollen release.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-situ pollen collections are very likely to be influenced by humidity (e.g. caused by rain events), mildew and insects after plants have been covered with collective containers [ 38 ]. To overcome these issues, grasses were kept in climate chambers during the actual pollen release.…”
Section: Methodsmentioning
confidence: 99%
“…Following Jung et al [ 38 ], pollen grains were mechanically extracted. Total soluble protein content was quantified using BCA test [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The role of air pollutants on this day-by-day variation in allergen levels remains poorly understood. Allergen levels are also likely to differ by species/cultivars ( Jung et al, 2018 ). The lack of precise information on allergen levels in the air may have contributed to the null findings.…”
Section: Discussionmentioning
confidence: 99%
“…The mean Der 1 to Der 2-ratio ranged from 0.4 to 20.5 among various manufacturers they examined. A study by Jung et al [15] looking at pollen chemistry showed that pollen ranges from 2.5-61% of protein by dry mass. Another study by Roulston et al [16] concluded that there was a negative correlation with percentage of protein in pollen grain to pollen grain volume and mass.…”
Section: Discussionmentioning
confidence: 99%